Perjalanan Karir Kesenimanan Siti Chairani Proehoeman Sebagai Penyanyi Soprano (Sebuah Biografi) - Kumala, Ofa Yutri; Martarosa, Martarosa; Nursyirwan, Nursyirwan (Jurnal Seni, Desain dan Budaya)
ABSTRACTThis research, is the career journey of Siti Chairani Proehoeman as a soprano who has taken part in various countries, and is a great teacher who is a role model for every student who specializes in studying in the field of sound art. Siti Chairani Prohoeman is an Indonesian citizen who is very influential in Malaysia, he created a movement about vocals in Malaysia, great enthusiasm Siti Chairani Proehoeman has made vocals a culture for Malaysia. The names of the countries that Siti Chairani Proehoeman often performed at concerts, operas and recitals are in Italy, Germany, the Netherlands, France, Finland, USA, Japan, South Korea, Thailand, Singapore, Malaysia, Indonesia. Siti Chairani Proehoeman already has several serial albums and her professional career is a Classical / Opera singer (Soprano). The factors of Siti Chairani Proehoeman became a famous soprano in various countries, namely family background, habits, environment and education. This study discusses Siti Chairani Proehoeman's career as a soprano in a biographical form. In this case the history of Siti Chairani Proehoeman's career as a soprano based on data, sources, informants and all matters relating to the life history of an artist. This research method, analytic description, case study, observer participation. The results showed that, in the practice of Siti Chairani Proehoeman's life based on a musicalological perspective and assisted through historical and biographical reviews, Siti Chairani Proehoeman's position was a famous soprano.Keywords : soprano, vocal art, singer and biography, Siti Chairani ProehoemanABSTRAKPenelitian ini, merupakan perjalanan karir kesenimanan Siti Chairani Proehoeman sebagai seorang soprano yang telah berkiprah di berbagai negara, dan merupakan guru besar yang menjadi panutan bagi setiap muridnya yang khusus belajar di bidang seni suara. Siti Chairani Prohoeman adalah seorang warga negara Indonesia yang sangat berpengaruh besar di Malaysia, beliau menciptakan pergerakan movement tentang vokal di Malaysia, semangat yang besar Siti Chairani Proehoeman telah menjadikan vokal sebagai kebudayaan bagi negara Malaysia. Nama negara-negara yang sering dilakukan Siti Chairani Proehoeman pada konser, opera dan recital adalah di Italia, Jerman, Belanda, Perancis, Firlandia, USA, Jepang, Korea Selatan, Thailand, Singapura, Malaysia, Indonesia. Siti Chairani Proehoeman sudah mempunyai beberapa album seriosa dan karir profesional beliau adalah seorang penyanyi Klasik/Opera (Soprano). Adapun faktor-faktor Siti Chairani Proehoeman menjadi soprano terkenal diberbagai negara yaitu faktor latar belakang keluarga, kebiasaan, lingkungan dan pendidikan. Penelitian ini membahas perjalanan karir Siti Chairani Proehoeman sebagai penyanyi soprano dalam bentuk biografi. Dalam hal ini sejarah perjalanan karir Siti Chairani Proehoeman sebagai penyanyi soprano berdasarkan data-data, sumber, informan dan segala hal yang berkaitan dengan sejarah kehidupan seorang seniman. Metode penelitian ini, deskripsi analitik, studi kasus, partisipasi observer. Hasil penelitian menunjukkan bahwa, dalam praktik kehidupan Siti Chairani Proehoeman berdasarkan pandangan musikologis dan dibantu lewat tinjauan sejarah serta biografi maka posisi Siti Chairani Proehoeman adalah? penyanyi soprano terkenal.Kata kunci: soprano, seni suara, penyanyi dan biografi, Siti Chairani Proehoeman